2019
DOI: 10.1002/gps.5195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, associated risk factors of depression and mental health needs among geriatric population of an urban slum, Cuttack, Odisha

Abstract: Objectives To find the prevalence of depression among elderly population of urban slum of Cuttack and to study its association with sociodemographic factors, comorbidities, and various life events and also to explore the mental health needs of the study subjects as perceived by them. Methods It was a cross‐sectional study carried out in the urban slum, Jobra of Cuttack city in Odisha. Simple random sampling was done using random number table to select the study subjects. Predesigned pretested questionnaire inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…The strongest factors that could af- Table 4. Continued Fatemeh Abdi, et al Mental health of women living in slum fect mental health according to the studies were related to household income and socioeconomic status, which were highlighted in 10 studies [16,17,21,23,26,30,34,35,37,38]. These studies indicated low income, poverty, and low socioeconomic status can lead to poor mental health in women.…”
Section: Structural Factorsmentioning
confidence: 97%
See 4 more Smart Citations
“…The strongest factors that could af- Table 4. Continued Fatemeh Abdi, et al Mental health of women living in slum fect mental health according to the studies were related to household income and socioeconomic status, which were highlighted in 10 studies [16,17,21,23,26,30,34,35,37,38]. These studies indicated low income, poverty, and low socioeconomic status can lead to poor mental health in women.…”
Section: Structural Factorsmentioning
confidence: 97%
“…The reviewed studies examined different aspects. Structural factors such as gender, level of education, age, social and economic status, household income, marital status, number of households, place of birth, occupation, religion, and place of residence were among the factors covered [16][17][18][19]21,[23][24][25][26][27][28][30][31][32]34,[36][37][38]. The strongest factors that could af- Table 4.…”
Section: Structural Factorsmentioning
confidence: 99%
See 3 more Smart Citations